H Optimal Coordination of Homogeneous Agents Subject to Limited Information Exchange - Madjidian, Daria; Mirkin, Leonid; Rantzer, Anders (IEEE transactions on automatic control, 2017)
Controllers with a diagonal-plus-low-rank structure constitute a scalable class of controllers for multi-agent systems. Previous research has shown that diagonal-plus-low-rank control laws appear as the optimal solution to a class of multi-agent H 2 coordination problems, which arise in the control of wind farms. In this technical note we show that this result extends to the case where the information exchange between agents is subject to limitations. We also show that the computational effort required to obtain the optimal controller is independent of the number of agents and provide analytical expressions that quantify the usefulness of information exchange.